Web Based Tour Package Selection Recommendation Information System Using Algorithmscontent Based Filtering - Al Dimas; Muhammad Alda (Universitas Islam Kuantan Singingi, 2025)
Advances in information technology have facilitated easier access to information in various fields, including tourism. One of the challenges faced by tourists is choosing a tour package that suits their preferences and needs amidst the many available options. This research aims to design and build aWeb-Based Tour Package Selection Recommendation Information Systemusing algorithmsContent-Based FilteringThis method works by matching user profiles based on their preferences with descriptions and attributes of available tour packages. The system was developed using the PHP programming language and MySQL database, and implemented on a web platform for widespread access. Test results show that the system is capable of providing tour package recommendations relevant to user preferences, thus facilitating quick and accurate decision-making. This system is expected to improve the user experience in selecting tour packages and make them more satisfying.